PENGARUH INDUSTRI GULA TERHADAP EKONOMI MASYARAKAT WAY TERUSAN KABUPATEN LAMPUNG TENGAH TAHUN 1997 - 2019 - Arif Budianto; Sumiyatun Sumiyatun (Swarnadwipa, 2019)
Economic dinamics are changes in the economic system from time to time, the existence of an industry in the midst of society is a potential for developing the community’s economy. The research objectives to be achieved are: (1) To analyze the history of the relationship between the community and sugar industry companies, (2) To describe the contribution of the sugar industry in Lampung too the surrounding community. This research method is qualitative research. Data and data sources were obtained from books, village community leaders as sources, documented, archives, and other sources that could assist in gathering research data information. The results of this study are (1) as a very large sugar industry, it really requires human resources as workes in the sugar industry, so the sugar industry plans to cooperate with the government through the Ministryof Transmigration in order to carry out a transmigration program araund the sugar industry. In return, the community is given agricultutal land which has been partnered with the company. (2) With the partnership cooperation, the community also gets income and social security. From the results of this study, it can be concluded that the economic situation of the Way Terusan community is improving because many are supported by the sugar industry in the middle of the community’s residence.